2023
DOI: 10.1128/spectrum.01681-23
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes of Blood-Feeding Triatomines in the Context of Their Predatory Relatives and the Environment

Abstract: This study places microbiomes of blood-feeding North American Triatoma vectors (Reduviidae) into a broader evolutionary and ecological context provided by related predatory assassin bugs (Reduviidae), another unrelated vector species (soft tick Ornithodoros turicata ), and the environment these arthropods coinhabit. For both vectors, microbiome analyses suggest three interrelated sources of bacteria, i.e., the microbiome of vertebrate nests as their natural habit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Since then, culturedependent (Lopez-Ordonez et al 2018), cultureindependent (da Mota et al 2012Gumiel et al 2015), and high-throughput sequencing approaches have been used to gain a more comprehensive view of the bacterial component of the microbiome. The latter have mostly used bacterial metabarcoding (Brown et al 2020;Díaz et al 2016;Kieran et al 2019;Lima et al 2018;Mann et al 2020;McCall et al 2018;Montoya-Porras et al 2018;Oliveira et al 2018;Orantes et al 2018;Rodríguez-Ruano et al 2018;Tarabai et al 2023;Waltmann et al 2019), a few have used DNA metabarcoding to identify various components simultaneously (bacteria, vertebrate hosts, parasite diversity and, in one case, triatomine bugs) (Dumonteil et al 2020(Dumonteil et al , 2018Murillo-Solano et al 2021), one metataxonomic study used shotgun pyrosequencing to describe cultivable bacteria (Carels et al 2017), and another metataxonomic study used an interesting Restriction-site Associated DNA sequencing (RADSeq)based analysis to simultaneously study the vector, the parasite, bacteria and feeding patterns (Orantes et al 2018) (reviewed by Salcedo-Porras et al 2020). Various of these studies have reported low bacterial diversity in the triatomine microbiome in comparison to other insect groups (da Mota et al 2012;Gumiel et al 2015;Lopez-Ordonez et al 2018).…”
Section: Kissing Bugs (Hemiptera: Reduviidae: Triatominae)mentioning
confidence: 99%
“…Since then, culturedependent (Lopez-Ordonez et al 2018), cultureindependent (da Mota et al 2012Gumiel et al 2015), and high-throughput sequencing approaches have been used to gain a more comprehensive view of the bacterial component of the microbiome. The latter have mostly used bacterial metabarcoding (Brown et al 2020;Díaz et al 2016;Kieran et al 2019;Lima et al 2018;Mann et al 2020;McCall et al 2018;Montoya-Porras et al 2018;Oliveira et al 2018;Orantes et al 2018;Rodríguez-Ruano et al 2018;Tarabai et al 2023;Waltmann et al 2019), a few have used DNA metabarcoding to identify various components simultaneously (bacteria, vertebrate hosts, parasite diversity and, in one case, triatomine bugs) (Dumonteil et al 2020(Dumonteil et al , 2018Murillo-Solano et al 2021), one metataxonomic study used shotgun pyrosequencing to describe cultivable bacteria (Carels et al 2017), and another metataxonomic study used an interesting Restriction-site Associated DNA sequencing (RADSeq)based analysis to simultaneously study the vector, the parasite, bacteria and feeding patterns (Orantes et al 2018) (reviewed by Salcedo-Porras et al 2020). Various of these studies have reported low bacterial diversity in the triatomine microbiome in comparison to other insect groups (da Mota et al 2012;Gumiel et al 2015;Lopez-Ordonez et al 2018).…”
Section: Kissing Bugs (Hemiptera: Reduviidae: Triatominae)mentioning
confidence: 99%